PERSEPSI ATAS RELEVANSI DAN PROSPEK KARIR MANAJEMEN DAKWAH : STUDI KASUS MAHASISWA MAGISTER UIN JAKARTA - Fadilah, Nurul; Ardani, Baharudin (JURNAL MANAJEMEN DAKWAH, 2024)
Da’wah Management program is designed to cultivate graduates who are proficient in managing religious institutions and contributing to various faith-based sectors. However, there remains a degree of uncertainty regarding the alignment between the program's academic focus and the career opportunities available in the job market. This study aims to explore alumni perceptions concerning the relevance of their education and the career prospects associated with a degree in Da’wah Management. Employing a qualitative approach, data were gathered through in-depth interviews with alumni from different graduating cohorts. The findings indicate that while some alumni consider their academic background relevant to their current roles, many encounter challenges in securing employment that aligns with their field of study. Among the key issues identified are limited job opportunities, a lack of public awareness and understanding of the discipline, and a curriculum that insufficiently addresses the development of digital competencies. Based on these insights, the study recommends fostering stronger partnerships between higher education institutions and relevant industries, enhancing the curriculum with practical, skill-based learning, and increasing outreach efforts to raise awareness of the professional pathways available to graduates of the Da’wah Management program.